2009
DOI: 10.1677/joe-09-0181
|View full text |Cite
|
Sign up to set email alerts
|

Improved insulin sensitivity by calorie restriction is associated with reduction of ERK and p70S6K activities in the liver of obese Zucker rats

Abstract: Calorie restriction (CR) improves obesity-related insulin resistance through undefined molecular mechanisms. Insulin receptor substrate (IRS)-1 serine/threonine kinases have been proposed to modulate insulin sensitivity through phosphorylation of IRS proteins. The aim of this study is to test the hypothesis that changes in the activity of IRS1 serine/threonine kinases may underlie the molecular mechanism of CR in improving insulin sensitivity. Obese and lean Zucker rats were subjected to 40% CR or allowed to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 49 publications
4
48
1
1
Order By: Relevance
“…Since inhibitory crosstalk between ERK1/2 and AMPK has been reported (Du et al, 2008), the increase in phospho-AMPK levels could be the result of the inhibition by GW501516 of the phosphorylation of ERK1/2 induced by the HFD, which is in agreement with our previous study reporting that www.intechopen.com GW501516 prevents LPS-induced ERK1/2 phosphorylation in adipocytes (Rodriguez-Calvo et al, 2008). It is important to note that a previous study found that obesity leads to increased hepatic ERK1/2 activity and that caloric restriction blunts this increase and improves insulin sensitivity (Zheng et al, 2009). In our study, the improvement in glucose tolerance caused by GW501516 was also accompanied by the reduction in phospho-ERK1/2 levels.…”
Section: Role Of Pparβ/δ In Lipoprotein Metabolismsupporting
confidence: 90%
“…Since inhibitory crosstalk between ERK1/2 and AMPK has been reported (Du et al, 2008), the increase in phospho-AMPK levels could be the result of the inhibition by GW501516 of the phosphorylation of ERK1/2 induced by the HFD, which is in agreement with our previous study reporting that www.intechopen.com GW501516 prevents LPS-induced ERK1/2 phosphorylation in adipocytes (Rodriguez-Calvo et al, 2008). It is important to note that a previous study found that obesity leads to increased hepatic ERK1/2 activity and that caloric restriction blunts this increase and improves insulin sensitivity (Zheng et al, 2009). In our study, the improvement in glucose tolerance caused by GW501516 was also accompanied by the reduction in phospho-ERK1/2 levels.…”
Section: Role Of Pparβ/δ In Lipoprotein Metabolismsupporting
confidence: 90%
“…39 Because of the reduced adiposity and enhanced glucose tolerance response measured in FIRKO mice, it was postulated that selective loss of insulin signaling in the adipose tissue may mimic calorie restriction conditions, 39 conditions shown to decrease circulating insulin. 27,28 In our model system, we demonstrate that reduced DILP production only during adulthood engenders differential regulation in aspects of glucose homeostasis mimicking the complex process seen in other, more complex animal models substantiating the use of an invertebrate model for studying relevant insulin action affecting systemic energy metabolism and longevity. With a set of molecular tools for monitoring systemic glucose homeostasis and insulin action in the adult fly established and validated, the identification and characterization of potentially novel molecular interventions that seek to regulate glucose homeostasis, energy metabolism and longevity should be permitted.…”
Section: Discussionmentioning
confidence: 52%
“…27, 28 We found that in adult IPC KD flies insulin sensitivity is largely intact as assessed by both unaltered Akt phosphorylation detected in peripheral flight muscle tissue and the ability of those flies to dispose of circulating glucose in response to insulin injection. Two conclusions may be drawn from those results.…”
Section: Discussionmentioning
confidence: 83%
“…In this study, we provide evidence demonstrating that hepatic Sort1 levels cannot only be changed by genetic homeostasis ( 27,28 ). Palmitate is an essential substrate for de novo synthesis of ceramides, and it is well documented that oversupply of saturated FFAs, mainly palmitate, results in elevated ceramides in the circulation and insulinresistant tissues in diabetic humans and rodent models ( 21 ).…”
Section: Discussionmentioning
confidence: 67%